NEAR ROOM-TEMPERATURE TEMPERATURE MAGNETOCALORIC EFFECT IN Pr₀.₆₃₋ₓHoₓSr₀.₃₇MnO₃ MANGANITES - LUDOȘAN, Alexandra; DEAC, I.G. (Studia Universitatis Babeș-Bolyai Physica, 2021)
Near room-temperature magnetic and magnetocaloric properties of the compounds Pr0.63-xHoxSr0.37MnO3 (x=0, 0.05) were investigated. The parent compound Pr0.63Sr0.37MnO3 has a large magnetocaloric effect around its Curie temperatures of about 300 K. Partially replacing of Pr3+ ions with Ho3+ ions in Pr0.63Sr0.37MnO3 gives rise to disorder which leads to the decrease of the Curie temperature without a significant reduction of the magnetocaloric effect. The samples were prepared by solid state reaction and were found to be single phase by x-ray diffraction. The magnetic measurements reveal paramagnetic to ferromagnetic second order phase transitions. For the sample with x = 0, the magnetic entropy change |ΔSM| was in the range from 1.91 J/kg٠K (RCP = 42 J/kg) for μ0 ΔH = 1 T to 4.86 J/kg٠K (RCP = 184 J/kg) for μ0 ΔH = 4 T. For the sample with x = 0.05, the magnetic entropy change |ΔSM| was in the range from 1.61 J/kg٠K (RCP = 57.9 J/kg) for μ0 ΔH = 1 T to 4.38 J/kg٠K (RCP = 236 J/kg) for μ0 ΔH = 4 T and Tc = 216 K. These values recommend these materials to be potential candidates to be used in near room-temperature refrigeration applications.